Protocol for a feasibility randomised trial of low-intensity interventions for antenatal depression: ADAGIO trial comparing interpersonal counselling with cognitive behavioural therapy - Sarah Johnson; Debbie Johnson; Jeff Round; Jonathan Evans; Jenny Ingram; Heather A O'Mahen; Hazel Taylor; Roslyn Law; Jenny Ford; Rebecca Hopley; Joel Glynn; Iryna Culpin (BMJ Open)
Introduction One in eight women suffer from depression during pregnancy. Currently, low-intensity brief treatment based on cognitive behavioural therapy (CBT) is the only talking treatment widely available in the National Health Service (NHS) for mild and moderate depression. CBT involves identifying and changing unhelpful negative thoughts and behaviours to improve mood. Mothers in our patient advisory groups requested greater treatment choice. Interpersonal counselling (IPC) is a low-intensity version of interpersonal therapy. It may have important advantages during pregnancy over CBT because it targets relationship problems, changes in role and previous losses (eg, miscarriage). We aim to compare CBT and IPC for pregnant women with depression in a feasibility study.Methods and analysis A two-arm non-blinded randomised feasibility study of 60 women will be conducted in two UK localities. Women with depression will be identified through midwife clinics and ultrasound scanning appointments and randomised to receive six sessions of IPC or CBT. In every other way, these women will receive usual care. Women thought to have severe depression will be referred for more intensive treatment. After 12 weeks, we will measure women’s mood, well-being, relationship satisfaction and use of healthcare. Women, their partners and staff providing treatments will be interviewed to understand whether IPC is an acceptable approach and whether changes should be introduced before applying to run a larger trial.Several groups of patients with depression during pregnancy have contributed to our study design. A patient advisory group will meet and advise us during the study.Ethics and dissemination Study results will inform the design of a larger multicentre randomised controlled trial (RCT). Our findings will be shared through public engagement events, papers and reports to organisations within the NHS. National Research Ethics Service Committee approved the study protocol.Trial registration number ISRCTN11513120.